The potential of nitric oxide releasing therapies as antimicrobial agents - Schairer, David O. (Landes Bioscience, 2012)
Nitric oxide (NO) is a short-lived, diatomic, lipophilic gas that plays an integral role in defending against pathogens. Among its many functions are involvement in immune cell signaling and in the biochemical reactions by which immune cells defend against bacteria, fungi, viruses and parasites. NO signaling directs a broad spectrum of processes, including the differentiation, proliferation, and apoptosis of immune cells. When secreted by activated immune cells, NO diffuses across cellular membranes and exacts nitrosative and oxidative damage on invading pathogens. These observations led to the development of NO delivery systems that can harness the antimicrobial properties of this evanescent gas. The innate microbicidal properties of NO, as well as the antimicrobial activity of the various NO delivery systems, are reviewed.